(untitled) (Experimental biology, 2020)
The dynamics of starch accumulation during the transition of plants from vegetation to the dormant period in the annual shoots of various groups of garden roses grafted on a Centifolia rose or on a Rosa canina, and on their own roots was studied. It was established that in ungrafted groud cover roses, after the maximum accumulation of starch in September, its hydrolysis is observed in October. Grafting on a Centifolia rose significantly speeds up this process. In roots of polyanthus and climbing roses, starch synthesis continues in October. In these roses grafted onto a Centifolia rose or on a Rosa canina, the dynamics of starch accumulation changes, which is expressed either in the suspension of its synthesis or in the starting the hydrolysis. In general, both in ground cover and in polyanthus and climbing roses, grafting provided better preparation of grafted material for winter than was observed in roses on their own roots. Keywords: garden rose, annual shoot, graft, starch, dynamics, preparation for winter.